Geis : a matter of life & death - Deacon, Alexis (Geis, 2016)
"The chief matriarch is dying. Drawing her last breath, she declares a contest: let fate decide the one worthy to rule. Fifty souls are summoned in the night; fifty souls bound to the same fate. But this is no ordinary trial... And so begins the first task. This supernatural historical fantasy is the first in an epic trilogy"--Cover.